Metabolism and ruminal parameters of Holstein x Gir heifers fed sugarcane and increasing levels of crude protein - Soares Queiroz, Maria Fernanda [UNESP]; Berchielli, Telma Teresinha [UNESP]; Signoretti, Ricardo Dias; Ribeiro, Andressa Ferreira [UNESP]; da Silva Morais, Jucileia Aparecida [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2012)
The objective of this study was to evaluate the effect of increasing levels of crude protein (CP) in the diet (13, 15, 19 and 22 g/100 g of dry matter, DM) on the metabolism and ruminal parameters of crossbred heifers fed forage sugarcane. Four crossbred Holstein x Gir heifers of average initial weight of 200 kg and average age of 14 months were used. The experimental design was in a 4 x 4 latin square. The intake values of DM, organic matter (OM), neutral detergent fiber (NDF) and non-fibrous carbohydrates (NFC) were not affected by the protein contents of the diet. The apparent and ruminal digestibility of DM and OM were affected by the protein content of the diet. Greater total apparent digestibility coefficient of CP (0.749) was observed for the content of 22 g CP/100 g DM, whereas the ruminal digestibility of CP was not affected by treatments. The efficiency of microbial protein synthesis was not different between the CP contents of the diet. There was increasing linear effect of the CP content in the diet on the plasma concentration of urea. The rumen pH of the heifers was similar between treatments, with an average of 6.3. The concentration of rumen ammonia nitrogen was affected by the protein content of the diet, with the highest averages at 22 and 19 CP/100 g DM (27.5 and 31.6 mg/dL); an average of 21.1 mg/dL in the diet with 15 g CP/100 g DM; and the lowest average observed in the diet containing 13 g CP/100 g DM, 14.0 mg/dL. It is recommended to use 13 g CP/100 g DM in the diet for crossbred Holstein x Gir heifers in the post-weaning phase consuming diets based on sugarcane, because this level promotes increase in the digestibility of the diet and lower concentrations of plasma urea nitrogen and ammonia nitrogen, showing better animal metabolism, in addition to a possible decrease in the cost of the diet.
Keywords: Digestibility; microbial synthesis; plasma urea; protein fractionation